Back Cover: Spontaneous and Widespread Electricity Generation in Natural Deep‐Sea Hydrothermal Fields (Angew. Chem. Int. Ed. 21/2017). Issue 21 (26th April 2017) - Yamamoto, Masahiro; Nakamura, Ryuhei; Kasaya, Takafumi; Kumagai, Hidenori; Suzuki, Katsuhiko; Takai, Ken
Abstract : Electricity generation is observed from sub‐seafloor hydrothermal fluids. In their Communication onpage 5725 ff., M. Yamamoto et al. show widespread and distant electron transfer from sub‐seafloor hydrothermal fluids to the seafloor by way of electrically conductive massive hydrothermal mineral deposits.